2018
DOI: 10.1001/jama.2018.3182
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Treatment of Male Hypogonadism

Abstract: Men with symptoms potentially consistent with hypogonadism are frequently encountered in clinical practice. The clinical features associated with true male hypogonadism are nonspecific and include impaired libido, erections, and fertility; reductions in lean muscle mass and bone density; loss of facial, axillary, and pubic hair; anemia; and changes in mood and vitality. The effects of testosterone on energy, physical performance, mood, and cardiometabolic factors continue to be explored, but in general, the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Based on serum testosterone levels, approximately 20%, 30%, and 50% of men aged 60, 70, and 80 are defined as biochemically hypogonadal, respectively (Salonia et al, 2019). Although exogenous testosterone administration can reverse several hypogonadism-associated symptoms (Mayor, 2016;Snyder et al, 2016), emerging evidence has revealed that it may also increase the risk of cardiovascular disease and cancer, and also impede spermatogenesis (Kolettis et al, 2015;Nguyen et al, 2015;Budoff et al, 2017;Sargis and Davis, 2018). Studies focusing on the mechanisms of testosterone formation can help identify potential targets for use in the treatment of hypogonadism.…”
Section: Introductionmentioning
confidence: 99%
“…Based on serum testosterone levels, approximately 20%, 30%, and 50% of men aged 60, 70, and 80 are defined as biochemically hypogonadal, respectively (Salonia et al, 2019). Although exogenous testosterone administration can reverse several hypogonadism-associated symptoms (Mayor, 2016;Snyder et al, 2016), emerging evidence has revealed that it may also increase the risk of cardiovascular disease and cancer, and also impede spermatogenesis (Kolettis et al, 2015;Nguyen et al, 2015;Budoff et al, 2017;Sargis and Davis, 2018). Studies focusing on the mechanisms of testosterone formation can help identify potential targets for use in the treatment of hypogonadism.…”
Section: Introductionmentioning
confidence: 99%
“…Male infertility can manifest in the form of premature ejaculation, hypoactive sexuality, erectile dysfunction, oligospermia, azoospermia, etc ., but its most common manifestation form is as oligospermia. In treating this condition, testosterone and other forms of hormone replacement therapy are often clinically employed due to their ability to stimulate/enhance sexual appetite in hypogonadal male patients [4, 5]. However, despite the proven efficacy of this replacement therapy in the management of hypoactive sexual desire [6], many patients still prefer to use natural plants because of the attendant undesirable side-effects associated with these hormonal therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, most treatment guidelines recommend against the initiation of TRT in patients with a history of or known risk factors for CaP. Guidelines recommend against T replacement in patients with metastatic or locally advanced CaP and in patients at high risk for recurrent CaP (4)(5)(6)(7)(8).…”
Section: Commentmentioning
confidence: 99%